Menggagas Pembelajaran Agama Kristen Berbasis Misiologi - Sembiring, Lena Anjarsari; Simon, Simon (Harati: Jurnal Pendidikan Kristen, 2022)
This paper specifically described the issue of initiating the study of Christianity based on missiology. This topic was reviewed because factually Christian education based on missiology was still not fully encouraged in religious learning in classes. This topic was discussed considering that there were still a lot of various tribes who had not been reached in missionary services. Obviously, this should not be the responsibility of missionary institutions alone, but religious institutions in the context of Christian education should also make a contribution and pay attention to it. In discussing this topic, the researchers used qualitative methods with a literature study approach. The description in discussing this article started with the Curriculum of Christian Religious Education leading to missiology. Then, the practice of mission-based learning was carried out for students in the classrooms. This was done to instill the concern of the Great Mandate from an early age. Besides, Christian Educators should live up to their missionary activities as their responsibility of their vocation as educators chosen by God to encourage the missionary movements. It was done to emulate the way how Jesus and the apostles taught but framed in missionary Tulisan ini secara spesifik menguraikan perihal menggagas pembalajaran agama Kristen berbass misiologi. Topik ini diulas karena secara faktual pembelajaran agama Kristen berbasis misiologi masih belum sepenuhnya digalakkan dalam pembelajaran agama di kelas. Topik ini dibahas mengingat masih banyak ditemukan berbagai suku belum terjangkau dalam pelayanan misi. Tentunya tanggung jawab itu tidak hanya dibebankan kepada lembaga misi, namun lembaga keagamaan dalam konteks pendidikan Kristen turut ikut andil memerhatikannya. Di dalam menguraikan topik ini peneliti menerapkan metode kualitatif dengan pendekatan studi literatur. Uraian pembahasan pada artikel ini dimulai dari, kurikulum Pendidikan Agama Kristen itu sendiri mengarah pada misiologi. Kemudian praktik pembelajaran berbasis misiologi dilakukan di dalam kelas bagi naradidik. Ini dilakukan untuk menanamkan sejak usia dini, kepedulian pada mandat Amanat Agung. Disamping itu, Pendidik Agama Kristen menghidupi kegiatan bermisiologi, sebagai bentuk tanggung-jawab panggilannya sebagai pendidik yang dipilih oleh Tuhan untuk ikut menggalakkan gerakan bermisiologi. Hal itu dilakukan untuk meneladani jejak Yesus dan para rasul yang mengajar namun terbingkai dalam gerakan misiologi.